2022
DOI: 10.5194/cp-18-485-2022
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude, frequency and climate forcing of global volcanism during the last glacial period as seen in Greenland and Antarctic ice cores (60–9 ka)

Abstract: Abstract. Large volcanic eruptions occurring in the last glacial period can be detected by their accompanying sulfuric acid deposition in continuous ice cores. Here we employ continuous sulfate and sulfur records from three Greenland and three Antarctic ice cores to estimate the emission strength, the frequency and the climatic forcing of large volcanic eruptions that occurred during the second half of the last glacial period and the early Holocene, 60–9 kyr before 2000 CE (b2k). Over most of the investigated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 78 publications
(135 reference statements)
2
37
0
Order By: Relevance
“…4); this gives an average of 3.4 per millennium. Although our method is identical in concept, we calculate rather more peaks greater than 20 mg m -2 (2.87/ka vs 2.21/kyr) for the period 9-60 ka than that estimated for EDC by previous work (Lin et al, 2022). This difference seems to arise because our method calculates higher integrals for smaller peaks, suggesting that the difference is related to the way that the background is calculated and/or the way that we deal with the width of each peak.…”
Section: The Frequency Of Eruptions Recorded In Antarcticamentioning
confidence: 72%
See 4 more Smart Citations
“…4); this gives an average of 3.4 per millennium. Although our method is identical in concept, we calculate rather more peaks greater than 20 mg m -2 (2.87/ka vs 2.21/kyr) for the period 9-60 ka than that estimated for EDC by previous work (Lin et al, 2022). This difference seems to arise because our method calculates higher integrals for smaller peaks, suggesting that the difference is related to the way that the background is calculated and/or the way that we deal with the width of each peak.…”
Section: The Frequency Of Eruptions Recorded In Antarcticamentioning
confidence: 72%
“…For Antarctica, using methods similar to those we describe later, the authors (Lin et al, 2022) found no significant change in eruption rate across the 60 kyr period.…”
mentioning
confidence: 70%
See 3 more Smart Citations